2018
DOI: 10.1186/s12891-018-2211-7
|View full text |Cite
|
Sign up to set email alerts
|

Cohort identification of axial spondyloarthritis in a large healthcare dataset: current and future methods

Abstract: BackgroundBig data research is important for studying uncommon diseases in real-world settings. Most big data studies in axial spondyloarthritis (axSpA) have been limited to populations identified with billing codes for ankylosing spondylitis (AS). axSpA is a more inclusive concept, and reliance on AS codes does not produce a comprehensive axSpA study population. The first objective was to describe our process for establishing an appropriate sample of patients with and without axSpA for developing accurate axS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…2 Plots of odds ratio for individual features over three years, by gap between the end of the three year window and the date of diagnosis / matching. Dotted lines indicate 95% confidence intervals for odds ratios secondary care records so we could not assess the reliability of GPs' diagnosis of AS, however in our experience GP practices tend not to code such diagnoses without specialist opinion and in a recent US study a over 80% of a sample of coded diagnoses of AS were confirmed on chart review [18]. It should be noted that the annual incidence (approximately 4 per 100,000 per year in adults aged 18-60 years) is compatible with the lifetime prevalence of approximately 15 per 10,000 observed in other studies [19,20].…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…2 Plots of odds ratio for individual features over three years, by gap between the end of the three year window and the date of diagnosis / matching. Dotted lines indicate 95% confidence intervals for odds ratios secondary care records so we could not assess the reliability of GPs' diagnosis of AS, however in our experience GP practices tend not to code such diagnoses without specialist opinion and in a recent US study a over 80% of a sample of coded diagnoses of AS were confirmed on chart review [18]. It should be noted that the annual incidence (approximately 4 per 100,000 per year in adults aged 18-60 years) is compatible with the lifetime prevalence of approximately 15 per 10,000 observed in other studies [19,20].…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…This meant that confidence intervals were wide and it is possible that we lacked statistical power to detect some potentially meaningful associations. The data was from stand-alone primary care records with no linkage to secondary care records so we could not assess the reliability of GPs' diagnosis of ankylosing spondylitis, however in our experience GP practices tend not to code such diagnoses without specialist opinion and in a recent US study a over 80% of a sample of coded diagnoses of AS were confirmed on chart review (18). It should be noted that the annual incidence (approximately 5 per 100,000 per year in adults aged 18-60 years) is compatible with the lifetime prevalence of approximately 15 per 10,000 observed in other studies (19,20).…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…This meant that confidence intervals were wide and it is possible that we lacked statistical power to detect some potentially meaningful associations. The data was from stand-alone primary care records with no linkage to secondary care records so we could not assess the reliability of GPs' diagnosis of AS, however in our experience GP practices tend not to code such diagnoses without specialist opinion and in a recent US study a over 80% of a sample of coded diagnoses of AS were confirmed on chart review (18). It should be noted that the annual incidence (approximately 4 per 100,000 per year in adults aged 18-60 years) is compatible with the lifetime prevalence of approximately 15 per 10,000 observed in other studies (19,20).…”
Section: Strengths and Limitationsmentioning
confidence: 92%